Recent advances in vascularized tumor-on-a-chip - Huang, Christina Bao Xian; Tu, Ting-Yuan (Frontiers in Oncology, 2023)
The vasculature plays a critical role in cancer progression and metastasis, representing a pivotal aspect in the creation of cancer models. In recent years, the emergence of organ-on-a-chip technology has proven to be a robust tool, capable of replicating in vivo conditions with exceptional spatiotemporal resolution, making it a significant asset in cancer research. This review delves into the latest developments in 3D microfluidic vascularized tumor models and their applications in vitro, focusing on heterotypic cellular interactions, the mechanisms of metastasis, and therapeutic screening. Additionally, the review examines the benefits and drawbacks of these models, as well as the future prospects for their advancement.